What mobile phone does to Western African music. ZikMali streaming platform: toward a new model of music distribution? - (:unkn) unknown (My University, 2023)
At the checkout of the Golden Price Market where I had gone to do some shopping, I found the latest issue of the Journal du Mali, neatly stacked. An article in the Economy section, titled 'ZikMali. Music Legally' 1 caught my attention. The content built on the words of Mohamed Diarra, introduced as the 'president and general manager of ZikMali', who had announced the opening of a 'platform and structure for the digital distribution of musical and cinematographic works' accessible from a mobile phone application. These few lines piqued my curiosity. I had, in fact, been investigating for a number of years what West African societies do with the digital in terms of knowledge transfer and production, the reconfiguration of social relations and cultural mediations. My aim being to reflect on the articulation between music, digital technology and culture, and in so doing revisit the question of innovative societies in the Global South. In Mali, as in most other West African countries, the popular music industry has seen major changes with the digitisation of musical production and listening supports: multiplication of digital audio workstation (DAW) studios and electronic music; shift from the almost exclusive use of the analogue cassette to the memory card (without the intermediate step the CD, except for international distribution); disappearance of the music reproduction and distribution system in favour of dissemination on social networks and streaming platforms. A new musical ecosystem is taking shape, in which the mobile phone is not only becoming the main mode of accessing music, but is also contributing to the transformation of creation processes, to listening, exchange and storage practices, to tastes, sociabilities and the imaginaries linked to music (Olivier, 2014; 2017b). 2
Keywords: African Research